Comparative analysis of the availability of popular social networking sites - Maciej Ciukaj; Maria Skublewska-Paszkowska (Journal of Computer Sciences Institute)
In the era of growing number of Internet users and the importance of social media, ensuring the accessibility of these platforms for all audiences has become a crucial aspect of digital inclusion. This article presents a study on the accessibility of Facebook, Instagram, X, and TikTok using Google Lighthouse and eye tracking. Two hypotheses were analyzed: H1, assuming a relationship between accessibility scores and the time to the first eye fixation on key elements of social networks, and H2, suggesting a relationship between accessibility and performance. Eye tracking research on a sample of 15 people showed that high accessibility does not always translate to ease of use, and no significant correlation between accessibility and platform performance was found.